Sosialisasi Personal Branding dan Desain Grafis oleh Mahasiswa KKN Uniwara dalam Meningkatkan Potensi UMKM Masyarakat Di Kelurahan Tapaan Kota Pasuruan - Siti Khodijah; Najma Jahira; Ummul Karima; Wardatuz Zahroh (Universitas Maritim AMNI Semarang, 2023)
Real Work Lecture (KKN) is a vehicle for the application and advancement of science and technology that takes place outside of school under certain time constraints, work processes, and requirements. Higher Education's Community Service Program is an effort to improve the content and quality of education for students and to gain more added value in higher education by carrying out several program activities, one of which is the socialization of personal branding and graphic design. It is envisaged that by implementing this Socialization, it will be possible to build local potential at the KKN location. The goal of this research was to discover and improve the local potential of the Tapaan Village region. The demographic and sample in this study are MSME-Practitioners and Tapaan Village business owners. Interviews, observation, and documentation were utilized to obtain data. This interview method seeks information about the SMEs that the community lives and the potential that exists in the Tapaan Village. According to the study's findings, the role of KKN is part of growing student competency as a kind of community service, particularly in Tapaan Village.